Aortoesophageal fistula with formation of secondary aortic pseudoaneurysm due to esophageal neoplasia: case report - Frizon, André; Schaffel, Esther Heloisa; Donato, Francisco; Bello, Rodrigo; Macagnan, Mauricio Rizzi; Silva, Fábio Goulart da; Sobrinho, Henrique Rosa (Brazilian Journal of Case Reports, 2024)
Aortoesophageal fistula as a cause of upper gastrointestinal bleeding is a very rare event with a high immediate mortality rate. Some of the causes include foreign bodies, post-surgical complications, and malignancy. The following case describes how esophageal cancer invaded the walls of the descending aorta, leading to the formation of a pseudoaneurysm that subsequently fistulized into the esophagus, secondary to radiotherapy treatment. This case highlights the importance of evaluating the thoracic aorta before and during radiotherapy treatments, to investigate the existence of aortic vascular compromise adjacent to the esophagus. If the existence of an aortic pseudoaneurysm is detected, radiotherapy treatment should be suspended until the pseudoaneurysm is corrected, reducing the lethality of patients undergoing advanced treatments.